Formulation and Evaluation of Delayed Release Enteric Coated Tablets of Tenatoprazole, by Optimizing the Plymers - Nikunja B Pati; Swapna Velivela; Vinyas Mayasa; Ravindra Babu Baggi (Shiraz University of Medical Sciences, 2020)
The present study was undertaken with an aim to formulate enteric coated tablets of Tenatoprazole (a novel proton pump inhibitor with an imidazopyridine ring) to improve bioavailability by avoiding degradation. Different core tablets were prepared using approved excipients by direct compression method and evaluated for different parameters like hardness, thickness, friability and disintegration time. Sub-coating was done for optimized formulation (F5) by using HPMC 5 cps with buildup of 3% w/w and finally enteric coating was done by using HPMCP, Eudragit L30 D55 and HPMC Acetate succinate (HPMCAS) with an average weight buildup of 5%, 8% and 10% w/w. all formulations were evaluated for different parameters like hardness, friability, thickness, disintegration time, drug content and dissolution studies and compared with marketed sample. Results indicated that, methacrylic acid polymers exhibited better dissolution rate than cellulose polymers. The optimized formulation was subjected to stability studies as per ICH guidelines for 3 months and was observed that no significant change was observed.